Capability Development Of Malang Regency Village-Owned Enterprises (Bumdes) - Florentina Ratih Wulandari (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2020)
This paper aimed to describe the capability development of Village-Owned Enterprises (BUMDes) in Malang Regency. The research method used was a qualitative method. Data were collected from key informants from the Malang Regency Office of Community Empowerment and Village, and BUMDes in Malang Regency. The study revealed that there were 203 BUMDes in Malang Regency. They were trained annually for BUMDes by the Ministry of Villages, the Development of Disadvantaged Areas and Transmigration of the Republic of Indonesia as part of capabilities development Malang Regency BUMDes, in collaboration with the Malang Regency Office of Community Empowerment and Villages. The problems often arose in the capabilities development of Malang Regency BUMDes were, (a) socialization and communication program factors had not reached the optimum level yet; (b) lack of human resources who were able to manage the BUMDes (c) they tended to depend on the leadership of the Village Chief; (d) the partnership was too dependent on the sponsor's intention. The limitations of the study were caused by the limited time and location, so it could not cover all regions and other stakeholders. Hence, the study results could not be generalized to other regions. The implications of the studies were to increase the effectiveness of Malang Regency BUMDes capability development and consider providing regular clinics with consultants at the District Office. To improve the efficiency of Malang Regency BUMDes capability development, it was necessary to disseminate a package of practical tools guidance and management training per District, in addition to Malang Regency Training. The originality of these findings was related to the wider picture of beneficial roles of dynamic capabilities and collaborative governance for optimal and sustainable economic empowerment of rural communities.